Does Public Policy Crowd Out Private Contributions to Public Goods? - Karine Nyborg; Mari Rege (Statistics Norway, Research Department, 2001)
It is sometimes claimed that individuals' contributions to public goods are not motivated by economic costs and benefits alone, but that people also have a moral or norm-based motivation. A number of studies indicate that such moral or norm-based motivation might be crowded out, or crowded in, by public policy. This paper discusses some models that can yield insight into the interplay between economic and moral or norm-based motivation for voluntary contributions to public goods, and compares their policy implications. We distinguish between four types of models: Altruism models, social norm models, models of commitment and the cognitive evaluation theory.
Keywords: D11; H41; Q28; 330; Private provision; altruism; social norms; commitment.